Mediasi dan Penyelesaian Sengketa Waris - Khosyi'ah, Siah; Azhari, Ahmad (El 'Ailaah, 2025)
The purpose of this study is to find out the procedures for implementing inheritance dispute resolution through mediation in Dombo Village, Sayung District, Demak Regency, to find out the role of community leaders in Dombo Village, Sayung District, Demak Regency in resolving self-help-based inheritance disputes. In this study, a qualitative research method is used, with the problem approach used is a socio-legal juridical approach (socio legal research), which is an approach to problems through legal research by looking at applicable legal norms and connecting with facts that exist in society in relation to the problems encountered in the research. Meanwhile, the data collection methods used in this study are interviews, documentation, and data analysis. The result of this research is that the settlement of inheritance disputes is resolved by Sulh, namely the settlement of disputes peacefully. The results of the dispute stated that in resolving family problems between the parties to the dispute, community leaders act as mediators or mediators who are neutral and better understand Islamic inheritance law and emphasize religious values about the importance of communication and deliberation in a conflict that occurs to prevent even greater conflicts.